CURRENT TRENDS IN THE DEVELOPMENT OF INNOVATION POTENTIAL OF DOMESTIC ENTERPRISES IN THE CONTEXT OF NATIONAL SECURITY - YUDINA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article focuses on the close relationship between industrial development and economic growth in the context of focus on innovative development. The structure of potential of domestic enterprises is studied, the main elements of which should be provided by close interrelations in the enterprise management system. The external and internal factors influencing the formation and development of the potential of domestic enterprises are singled out. The problems of ensuring the potential of enterprises in the industrial sector of the national economy are studied. The importance of forming a national innovation system is emphasized. Approaches to diagnostics of realization of innovative potential of the enterprise in the context of national security of the country are substantiated. The main factors that hinder the development of innovation potential of domestic enterprises are identified. The components of the innovation potential management system are studied, including the subsystems of planning, motivation, organization, monitoring, control and the subsystem of diagnostics of innovation potential.
Keywords: industrial enterprises; innovation potential; factors of enterprise potential development; national security innovation potential management system